Effect of deconstructed tire under sleeper pad on railway ballast degradation under cyclic loading. Issue 136 (September 2020) - Esmaeili, Morteza; Shamohammadi, Armin; Farsi, Saeid
Abstract: In this paper, the effect of different thicknesses of Deconstructed Tires Under Sleeper Pads (DT-USP) and different Unconfined Compressive Strength (UCS) values of mother rocks of ballast aggregates were studied in the degradation of railway ballast. For this purpose, in the first step, both static and dynamic bedding modulus of DT-USP's were extracted in the laboratory according to DIN standard requirements. In continuation, the physical and mechanical properties of the three different ballast types taken from Shahriar, Anjilavand, and Kouhin quarries in Iran were obtained via a series of standard lab tests. The UCS of core specimens taken from the mother rocks of the mentioned queries were ranked as low (159 MPa), medium (216 MPA), and high (285 MPa) respectively. Finally, 36 ballast box test experiments with and without the presence of DT-USPs in three thicknesses of 7, 11, and 13 mm were carried out and their results were compared up to 200, 000 loading cycles to investigate the cyclic behavior of ballast samples. Experiment results were elicited in the form of settlement, Hardin breakage index (Br), ballast stiffness, and ballast Damping Ratio (DR). The results demonstrate for ballast of Shahriar quarry by increasing of the DT-USP's thickness from 7 to 13 mm, settlement, Br, and stiffness have decreased by 38.4%, 6.9%, and 80.5% respectively and DR has increased by 199.2% while these reported percentages, i.e. settlement, Br, and Stiffness have decreased and DR has increased after strengthening the ballast mother rock in the cases of Anjilavand and Kouhin quarries. On the other side, based on the achieved results for all three categories of ballast strengths, the DT-USP with 11 mm thickness has shown the most suitable performance. Highlights: Effect of deconstructed tire under sleeper pad is investigated on ballast cyclic behavior. The ballast breakage and settlement is monitored in ballast box test. Three types of stiff, medium and soft ballast rock is investigated in the tests. By testing various DT-USPs thicknesses, an optimum thickness is introduced for all ballast types. A logarithmic equation is proposed for ballast settlement relating to the load cycles and DT-USP stiffness.